1999
DOI: 10.1046/j.1365-2125.1999.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Cough and angiotensin II receptor antagonists: cause or confounding?

Abstract: Aims Cough is one of the most frequent side effects associated with angiotensin converting enzyme inhibitors (ACEIs) but is not thought to be associated with losartan, an angiotensin II receptor antagonist (ARA). This study compares reports of cough with losartan and three ACEIs used in general practice. Methods Studies have been conducted for losartan, and three ACEIs enalapril, lisinopril and perindopril, using the technique of Prescription-Event Monitoring. Patients were identified using dispensed prescript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 5 publications
2
31
0
6
Order By: Relevance
“…15 Cough is a class effect of ACE inhibitors to the nonspecificity of the ACE. One clinical trial has shown that the incidence of cough under valsartan was similar to that observed under diuretic therapy, but significantly lower than that observed under lisinopril.…”
Section: Discussionmentioning
confidence: 99%
“…15 Cough is a class effect of ACE inhibitors to the nonspecificity of the ACE. One clinical trial has shown that the incidence of cough under valsartan was similar to that observed under diuretic therapy, but significantly lower than that observed under lisinopril.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that carry-over effects from previously administered ACE inhibitors account for many of the cases of cough reported during the early days of treatment with losartan. 9 Dizziness was the most frequently reported ADR and is already noted in the Summary of Product Characteristics for losartan. 2 There were also occasional reports of vertigo, labyrinthitis and tinnitus possibly associated with losartan.…”
Section: Discussionmentioning
confidence: 92%
“…This was borne out by one study that compared the emergence of coughing in patients on losartan vs. three ACE inhibitors commonly prescribed in general practice (enalapril, lisinopril, and perindopril). Rates of cough between Day 8 and Day 60 were significantly higher in patients on the ACE inhibitors vs. the AT 1 receptor antagonist [53]. Similarly, in a randomised, double-blind, double-dummy, placebo-controlled study involving 119 hypertensives, those patients taking enalapril 20 mg demonstrated a statistically higher incidence of cough compared to patients on telmisartan 80 mg [54].…”
Section: Effects On Heart Failurementioning
confidence: 99%